The Effect of Leadership and Compensation on Employee Performance - Kusumo, Bayu Hadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The study aims to understand the relationship between leadership, performance, and compensation in an organization. Job Performance refers to the total performance of an individual or group within a specific time frame. Performance is influenced by the output produced, while leadership is the ability to influence the performance of a group. Research has shown that leadership has significant effects on employee performance, motivation, and performance. Compensation is another factor that influences employee performance. It is a form of reward that motivates employees and is essential for understanding the performance of an organization. Research has also shown that a well-structured compensation package can improve employee performance. The study also highlights the importance of understanding the relationship between leadership, compensation, and performance in an organization. It suggests that organizations should focus on enhancing their leadership and compensation to achieve their goals. In conclusion, the study highlights the importance of understanding the relationship between leadership, compensation, and performance in an organization.